Natural Polyphenols: Chemical Classification, Definition of Classes, Subcategories, and Structures. (3rd December 2019) - Singla, Rajeev K; Dubey, Ashok K; Garg, Arun; Sharma, Ramesh K; Fiorino, Marco; Ameen, Sara M; Haddad, Moawiya A; Al-Hiary, Masnat
Abstract: Background: Polyphenols are natural compounds synthesized exclusively by plants with chemical features related to phenolic substances and eliciting strong antioxidants properties. Objective: The aim of this paper is to give a reliable overview of the chemical classification of natural polyphenols. Methods: Literature survey was done through google scholar, pubmed and scopus search engine. Results and Discussion: These molecules or classes of natural substances are characterized by two phenyl rings at least and one or more hydroxyl substituents. This description comprehends a large number of heterogeneous compounds with reference to their complexity. Therefore, polyphenols can be simply classified into flavonoids and non-flavonoids, or be subdivided in many sub-classes depending on the number of phenol units within their molecular structure, substituent groups, and/or the linkage type between phenol units. Polyphenols are widely distributed in plant tissues where they mainly exist in form of glycosides or aglycones. The structural diversity of flavonoid molecules arises from variations in hydroxylation pattern and oxidation state resulting in a wide range of compounds: flavanols, anthocyanidins, anthocyanins, isoflavones, flavones, flavonols, flavanones, and flavanonols.